LIMESTONE OF BUKIT KAMANG AS A CALCIUM SOURCE FOR LAYING HENS - Khalil, K.; Anwar, S. (Journal of the Indonesian Tropical Animal Agriculture, 2009)
A feeding trial was conducted to study the use of natural limestone meal originated from Bukit Kamanglocated at Agam district of West Sumatra to substitute fresh water oyster shell as the main source ofcalcium in diet of laying hens. The mineral feed formula, as treatments, composed of limestone in combinationwith freshwater oyster shell in five different percent ratios: 100:0; 75:25; 50:50; 25:75 and 0:100. The mineralswere mixed in the level of 6 % into basal diet composed mainly corn, rice bran and concentrates. The fiveexperimental diets were then fed to 150 laying hens. They were divided into 5 groups; each group wassubdivided into 3 replicates groups containing 10 hens. Parameters measured included: feed intake, eggproduction, FCR, eggshell quality, Ca and P retention, tibia bone mineralization. Results showed the nutritivevalues of limestone of Bukit Kamang as mineral source of laying hen diet were found not significantlydifferent from those of oysters shell. The hens fed with diet supplemented with Bukit Kamang’s limestonetended to give better laying performances than those of supplemented with fresh water oyster shell. Thelaying performances, egg shell quality and Ca and P retentions did not significantly improved, when limestonewas mixed by oyster shell.